The impact of foreign direct investment on the livelihoods of workers in the manufacturing sector of Lesotho - Kamara, Ishmail Bassie (University of the Free State)
Abstract not available
Investments, Foreign -- Lesotho
Keywords: Investments, Foreign -- Lesotho; Manufacturing industries -- Lesotho